STRESS MODELING IN COMPOSITE PRODUCTS USING STANDARD OPTICALLY SENSITIVE MATERIAL - Elifkhan K. Agakhanov; Nazhmudin S. Magomedeminov; Rustam G. Radzhabov (Вестник Дагестанского государственного технического университета: Технические науки)
Abstract. Objectives The problem of physically modelling stresses in a compound solid body of revolution having a complex shape and with a complex load distribution is considered. According to the similarity criteria of stress, deformations and displacements from the volume forces decrease proportionally to the scale of similarity of geometric dimensions, which complicates their direct modelling by the photoelasticity method typically using models made from epoxy materials. Methods Based on the principle of the independent action of the forces, the initial problem is represented as the sum of two problems. In the first uniform problem, the stresses in the body of revolution from the centrifugal forces are simulated by the conventional “freezing” method. In order to solve the second nonuniform problem, the stresses in the region of the model, corresponding to the acting centrifugal forces, are “frozen”. The models are glued in a natural state at room temperature, and the compound model is annealed. Results The band patterns in sections as well as components of radial, tangential and axial stresses on contours and in sections of models are obtained by the methods of normal transmission and numerical integration of the equilibrium equation. According to the modelling criteria, the formula for the transition from stresses in models to stresses in the natural structure is established. The results of the analysis of the effect of a body's material density ratio on the stress state of the entire structure are obtained. Conclusion  Axial stresses have insignificant value as compared to radial and tangential stresses; in addition, the ratio of the densities of the compound body has both a quantitative and qualitative influence on the stress state of the structure.